Distinct DNA Methylation Patterns of Subependymal Giant Cell Astrocytomas in Tuberous Sclerosis Complex - Bongaarts, Anika; Mijnsbergen, Caroline; Anink, Jasper J.; Jansen, Floor E.; Spliet, Wim G.M.; den Dunnen, Wilfred F.A.; Coras, Roland; Blümcke, Ingmar; Paulus, Werner; Gruber, Victoria E.; Scholl, Theresa; Hainfellner, Johannes A.; et al. (Cellular and Molecular Neurobiology, 2021)
Tuberous sclerosis complex (TSC) is a monogenic disorder caused by mutations in either the TSC1 or TSC2 gene, two key regulators of the mechanistic target of the rapamycin complex pathway. Phenotypically, this leads to growth and formation of hamartomas in several organs, including the brain. Subependymal giant cell astrocytomas (SEGAs) are low-grade brain tumors commonly associated with TSC. Recently, gene expression studies provided evidence that the immune system, the MAPK pathway and extracellular matrix organization play an important role in SEGA development. However, the precise mechanisms behind the gene expression changes in SEGA are still largely unknown, providing a potential role for DNA methylation. We investigated the methylation profile of SEGAs using the Illumina Infinium HumanMethylation450 BeadChip (SEGAs n = 42, periventricular control n = 8). The SEGA methylation profile was enriched for the adaptive immune system, T cell activation, leukocyte mediated immunity, extracellular structure organization and the ERK1 & ERK2 cascade. More interestingly, we identified two subgroups in the SEGA methylation data and show that the differentially expressed genes between the two subgroups are related to the MAPK cascade and adaptive immune response. Overall, this study shows that the immune system, the MAPK pathway and extracellular matrix organization are also affected on DNA methylation level, suggesting that therapeutic intervention on DNA level could be useful for these specific pathways in SEGA. Moreover, we identified two subgroups in SEGA that seem to be driven by changes in the adaptive immune response and MAPK pathway and could potentially hold predictive information on target treatment response.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Low-grade glioma; Methylation; RNA-sequencing; SEGA; TSC